Molecular Phylogeny and Characteristics of Methanogens from a Palm Oil Mill Anaerobic Tank - Tabatabaei, Meisam (2009)
This study was set up to investigate the phylogeny of and characterize the methanogenic population in anaerobic tank for treating palm oil mill effluent. In this study, environmental DNA was extracted and purified from wastewater sludge by using a simplified and less time consuming procedure (Malaysian Patent Pending Number: PI20082842 filed on 30/07/2008) and the results obtained were compared to that of other three existing protocols i.e. Ogram et al., Tsai and Olson, and Jacobsen and Rasmussen methods which are normally used for environmental samples. The DNA isolated from the palm oil mill anaerobic tank in FELDA Serting Hilir, was used for determining the molecular phylogeny of methanogenic archaea by using culture-independent analysis of the 16S rRNA genes amplified directly from sludge. Restriction fragment length polymorphism (RFLP) analysis, denaturing gradient gel electrophoresis (DGGE) and fluorescent in situ hybridization (FISH) were also used in combination which made the present study, the first wide-scale study carried out in Malaysia. 1260-bp 16S rRNA PCR products were cloned and sequenced. Phylogenetic analysis showed the microbes were closely affiliated with known cultured methanogenic Archaea, Methanosaeta concilii. Based on RFLP (HaeIII) analysis, just a few clones (clone SamaliEB; Genebank Accession Number: EU580025) seemed to be new species or at least new strains of Methanosaeta. This was also confirmed by DGGE analysis which showed the presence of M. concilii and Methanosarcina. sp. FISH was carried out using specifically designed 16s rRNA probes to target methanogens and bacteria. The results were in line with DGGE analysis and revealed the presence of two types of methanogens including M. concilii and Methanosarcina sp. in the anaerobic tank. Quantitative FISH showed that M. concilii had a population of 1.4 x 108/ml of wastewater sludge, while Methanosarcina sp. was 2 x 105/ml of wastewater sludge. This could be the reason of failing to get it cloned as for each 1000 clones of Methanosaeta, there was just one clone of Methanosarcina and therefore, the probability of picking up a clone affiliated to Methanosarcina was approximately 0.1 %. FISH helped to elucidate the association of methanogens and bacteria together. The findings of this study helped to understand the microbial population of the anaerobic tank for treating POME in Malaysia. The results indicate that filamentous acetate-utilizing methanogens detected in the POME anaerobic tank belong to the genus Methanosaeta based on the cell-morphology, and the phenotypic and phylogenetic characteristics described above. The data obtained also suggest that Methanosaeta is the most abundant methanogen in POME anaerobic digestion and that it plays an important role in methane production from acetate and its optimum growth conditions should be considered when an attempt is made to treat POME anaerobically. In future, these findings will provide the chance to optimize the anaerobic tank conditions to increase the methane production and “carbon oxygen demand” (COD) removal.